On the right nucleus of Petit algebras - Owen, Adam (2022)
Let D be division algebra over its center C, let σ be an endormorphism of D, let δ be a left σ-derivation of D, and let R=D[t; σ, δ] be a skew polynomial ring. We study the structure of a class of nonassociative algebras, denoted by Sf, whose construction canonically generalises that of the associative quotient algebras R/Rf where f ∈ R is right-invariant.